Pencegahan Perundungan/Bullying di Institusi Pendidikan: Pendekatan Hak Asasi Manusia (HAM) - Siregar, Ehdatul Puadi; F, Firman; Sukma, Dina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to study the phenomenon of bullying in schools. Departing from the condition of